A new species of Mikania (Eupatorieae, Asteraceae) from the southwestern Minas Gerais, Brazil - Oliveira, Caetano Troncoso; Nakajima, Jimi Naoki; Pirani, José Rubens (Phytotaxa, 2016)
Mikania fasciculata C.T. Oliveira & Pirani, a new erect species of this mostly vining genus, is described and illustrated. Mikania fasciculata is a subshrub known from the Serra da Canastra and surrounding areas in Minas Gerais, southeastern Brazil. It is closely related to M. thapsoides DC. but differs from it by the leaves narrowly elliptic, glabrous, with narrowly cuneate to cuneate base (vs. leaves deltoid, pilose on the abaxial surface, with attenuate to hastate base).